2020
DOI: 10.1038/s41419-020-02779-1
|View full text |Cite|
|
Sign up to set email alerts
|

Ciclopirox activates PERK-dependent endoplasmic reticulum stress to drive cell death in colorectal cancer

Abstract: Ciclopirox (CPX) modulates multiple cellular pathways involved in the growth of a variety of tumor cell types. However, the effects of CPX on colorectal cancer (CRC) and the underlying mechanisms for its antitumor activity remain unclear. Herein, we report that CPX exhibited strong antitumorigenic properties in CRC by inducing cell cycle arrest, repressing cell migration, and invasion by affecting N-cadherin, Snail, E-cadherin, MMP-2, and MMP-9 expression, and disruption of cellular bioenergetics contributed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 50 publications
1
26
0
Order By: Relevance
“…Proteome analyses of HPV16-positive SiHa cervical cancer cells reveal that CPX downregulates factors involved in OXPHOS, in line with its iron-chelating potential [ 35 ], and stimulates factors involved in glycolysis. These findings are also supported by a recent study showing that CPX inhibits mitochondrial respiration and promotes the glycolysis rate in colorectal cancer cells [ 22 ]. Due to OXPHOS inhibition, CPX-treated cells may react particularly sensitive to glucose scarcity.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Proteome analyses of HPV16-positive SiHa cervical cancer cells reveal that CPX downregulates factors involved in OXPHOS, in line with its iron-chelating potential [ 35 ], and stimulates factors involved in glycolysis. These findings are also supported by a recent study showing that CPX inhibits mitochondrial respiration and promotes the glycolysis rate in colorectal cancer cells [ 22 ]. Due to OXPHOS inhibition, CPX-treated cells may react particularly sensitive to glucose scarcity.…”
Section: Discussionsupporting
confidence: 81%
“…Among others, CPX inhibits the enzymes ribonucleotide reductase [ 17 ] and deoxyhypusine hydroxylase [ 19 ], downregulates the cell cycle regulators cyclin D1 and E [ 15 ], and inhibits mTORC1 signaling [ 8 , 20 ]. Furthermore, potentially adding to their anti-tumorigenic effects, CPX and other iron chelators can inhibit mitochondrial oxidative phosphorylation (OXPHOS), probably due to decreased activity and expression of the iron-containing enzymes comprising the mitochondrial respiratory complexes [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…ER stress is considered as one of the mechanisms contributing to ROS-mediated cell death (Qi et al, 2020;Zhao et al, 2020). Therefore, we measured the levels of ER stressrelated proteins in DU145 cells.…”
Section: Iatl and Cisplatin Co-operate To Activate Er Stressmentioning
confidence: 99%
“…CPX can induce cell death in a variety of cancers 3 6 ; for example, CPX inhibits tumor growth in xenografts of the human breast cancer cell line, MDA-MB231 3 . Our previous study reported that CPX can activate PERK-dependent endoplasmic reticulum (ER) stress to induce cell death and overcome chemoresistance in colorectal cancer cells 7 . In a phase I clinical trial, CPX showed efficacy and tolerability in the treatment of patients with relapsed or refractory hematologic malignancies 8 .…”
Section: Introductionmentioning
confidence: 99%